Ilmu Dalam Pandangan Islam - Gusmaletri; Ratna Sari, Esi; Sartati (Universitas Majalengka, 2024)
Nature is increasingly modern and advanced, and through this development and advancement, technology and science are also increasingly advanced. According to the Islamic perspective, knowledge is important and must be carried out in appropriate ways. If science does not have an Islamic perspective, physical and non-physical instability can arise. The aim of this research is to explore the nature of science from an Islamic perspective using the literature study method. This research investigates the basic concepts and principles of technology and knowledge contained in Islamic teachings through qualitative research methods. In order to obtain a good interpretation of religious perspectives on advances in technology and knowledge, and in what way these can be linked to aspects of Islam, a number of Islamic literary sources were studied. The results of this study are intended to provide a more specific understanding of the way Islam views its role and influence on technology and knowledge for human and social prosperity. This study can help gain a broader understanding of how technology, science and religious aspects interact through an Islamic perspective.